Cross protection between Trichophyton rubrum and Candida albicans in mice: Alwan, M.J. and Nabhan, S. - J., Alwan M. (The Iraqi Journal of Veterinary Medicine, 2006)
In order to know the cross –protection between antigene of T.rubrum andC.albicans,17 mice were used and they were divided into (3) groups,1st group(7animals) was immunized with T.rubrum antigen,two doses, and injected S/Cwith virulent C. albicans,the 2nd group (5 animals) was infected withC.albicans and considered as positive control,3rd group was served as negativegroup which injected 0.5 ml of sterile normal saline s /c The results showedthat the antigen of T.rubrum stimulated a good immune response inimmunized mice against C.albicans.